Artificial Intelligence Dalam Proses Recrutment Dan Seleksi Karyawan : Systematic Literature Review - Juhari; Mochammad Isa Anshori; Helmi Buyung Aulia Safrizal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract: The aim of this research is to analyze the application of Artificial Intelligence in the employee recruitment and selection process. The research method used in this research is the Systematic Literature Review (SLR) Method using the Publish Or Perish 8 (POP) Application and Vos Viewer. Researchers searched the database from Google Scholar for the period 2015 – 2022. Obtained 200 journals then carried out data reduction using inclusion and exclusion criteria to obtain 11 journals that would be reviewed. The results of this research state that artificial intelligence in the recruitment and selection process is very good to use in carrying out the initial recruitment and selection process because it will impact the efficiency of time, energy and costs for the company, but in the final selection it still requires a human recruiter, not IA because IA is difficult to adapt. regarding language and culture which will result in bias in decision making. The tools that are often used in multinational companies are Job Agrigator software, candidate assessman software and ATS (Applicant tracking software).